Globalization and the Politics of Identity in India (Pearson Longman, 2008)
Globalization and the Politics of Identity in India features sixteen original essays that discuss the political, religious, social, and cultural effects of globalization. It includes perspectives from political science, history, sociology, economics, and international relations; identity politics in Kashmir, Punjab, North Bengal, Rajasthan and the North-East, as well as among the diaspora. It also explains liberalization and privatization, the impacts of foreign direct investment and various tendencies brought about by globalization, such as Unitarianism, majoritarian nationalism and multiculturalism